Study on steel dust as filler material in cement based masonry - Ooi, Chun Shu (2015)
Portland composite cement is a cement with a wide range of application in various concrete building projects, due to its good strength performance for both general purpose and structural concrete applications. With a composite material that combines concrete with steel reinforcements, it provides a strong, durable building material that could cater for both compressive and tensile stress. Disposal of waste materials has become a major concern, where its process should be done with an appropriate way without giving negative effect to the environment. One example of this industrial by-product is steel dust, the by-product of refining metals and making alloys. This study deals with the experimental investigation on strength gaining characteristics of masonry with the addition of steel dust. The purpose of the study was to identify the optimum proportion of steel dust and analyse its effect to the compressive strength of masonry bricks. Compressive strength of masonry bricks is considered as a suitable measure to determine the rate of strength gain of bricks with age and different addition of steel dust composition. The steel dust used in the research was obtained from steel industry Kuantan Wire Products Sdn.Bhd in Semambu, Kuantan. There were five different dosages of steel dust in the mortar mix that was based on the volume fraction of fine aggregate, which were 0, 2.5, 5, 7.5, 10% (0, 35, 70, 105, 140 kg/m3). Based on the experimental results, particle size distributions of aggregates with the inclusion of steel dust presented insignificant effect to the compressive strength of cement brick. However in the workability test, inclusion of steel dust had a significant effect on the wet mixture and showed the fluctuated trend. Brick with 5% of steel dust inclusion has a higher compressive strength than others mixtures. For porosity test the brick with 5% of steel dust has lowest permeable space voids than others mixture. Conclusively, compressive strength and porosity performance of cement brick have shown the good potential of steel dust as filler in this construction material.